Kidney Stones: A Fetal Origins Hypothesis. (December 2013) - Howles, Sarah A; Edwards, Mark H; Cooper, Cyrus; Thakker, Rajesh V
ABSTRACT Kidney stones are common, with a multifactorial etiology involving dietary, environmental, and genetic factors. In addition, patients with nephrolithiasis are at greater risk of hypertension, diabetes mellitus, metabolic syndrome, and osteoporosis, although the basis for this is not fully understood. All of these renal stone–associated conditions have also been linked with adverse early‐life events, including low–birth weight, and it has been suggested that this developmental effect is due to excess exposure to maternal glucocorticoids in utero. This is proposed to result in long‐term increased hypothalamic‐pituitary‐axis activation; there are mechanisms through which this effect could also promote urinary lithogenic potential. We therefore hypothesize that the association between renal stone disease and hypertension, diabetes mellitus, metabolic syndrome, and osteoporosis may be related by a common pathway of programming in early life, which, if validated, would implicate the developmental origins hypothesis in the etiology of nephrolithiasis. © 2013 American Society for Bone and Mineral Research.